The Role of Prefabricated Materials in Architecture During the Pandemic and Post-Pandemic - Mochamad Faisal Ramadhianto; Dede Risman; Dhimas Bimantoro; Dedeng Hirawan; Rizky Jumansyah (Universitas Komputer Indonesia, 2021)
The purpose of this study is to determine and analyze how big the role of prefabricated materials in increasing construction efficiency in architecture, especially in the post-pandemic era. This research was conducted using qualitative methods because it relates to the views of researchers regarding to the relationship between prefabricated materials and post-pandemic phenomenon. The results obtained from this research are the application of prefabricated material technology that can help the construction process in architecture to be faster in several aspects. The presence of prefabricated materials in architecture, especially post-pandemic, can make the construction process faster in terms of time and installation. The presence of prefabricated materials in architecture, especially post-pandemic, can make the construction process faster in terms of time and installation. Therefore, the use of prefabricated materials is very well applied both during the pandemic and post-pandemic because it can break down the processing time faster so as to minimize the crowd of workers in the field. The final result of this research is to find out how big the role of prefabricated materials in architecture is to make work in the field more efficient and minimize crowds during the pandemic or post-pandemic period. We hope that this research can be useful for the architectural world regarding the advantages of applying prefabricated materials during the pandemic and post-pandemic era.